Giant cell tumor of the sphenoid bone mimicking a pituitary tumor. - Wilbur, A C; Choi, K H; Tan, W S; Jafar, J J; Spigos, D G (American Journal of Neuroradiology, 1986)
300 Multiple ChoicesThis is a pdf-only article and there is no markup to show you.full-text.pdf